On Numismatic Findings from the Southern Part of the Province of Dalmatia (Examples from the Area of Eastern Herzegovina) - Samardžić, Gligor M. (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
This paper presents the data about the numismatic findings from the area of the Roman province of Dalmatia (Eastern Herzegovina). With this supplement we present the unpublished and published ancient coins finds that have been discovered in the area of Eastern Herzegovina. The interpretation and publishing of numismatic sources are significant for the deliberation on the circulation of money and the representation of mints in the south of the province of Dalmatia in ancient times. The lack of written historical sources on the economic and political conditions is complemented by these old monetary emissions. The Roman conquest of and rule over the Province of Illyricum have contributed to the discovery of a significant ammount od Roman coins in the area of present-day Eastern Herzegovina.